The effect of aging on the center-of-pressure power spectrum in foam posturography. (12th January 2015) - Fujimoto, Chisato; Egami, Naoya; Demura, Shinichi; Yamasoba, Tatsuya; Iwasaki, Shinichi
Highlights: We assess aging effect on center-of-pressure power spectrum in foam posturography. Especially, the eyes open/foam rubber condition highlights age-related changes. Age-related changes were found in not only older but early-middle-aged subjects. Abstract: To assess age-related frequency-domain characteristics of the sway of center of pressure (COP) in foam posturography, two-legged stance tasks were performed by 163 controls in 4 conditions: eyes open with and without foam rubber, and eyes closed with and without foam rubber. The areas under the curve (AUCs) of power spectral density of the COP were calculated across low frequency (≥0.02 Hz and <0.1 Hz, LF-AUC), middle frequency (≥0.1 Hz and <1 Hz, MF-AUC) and high frequency (≥1 Hz and <10 Hz, HF-AUC) ranges. We categorized the controls into 7 age groups and analyzed each AUC in the 4 conditions. MF- and HF-AUCs tended to show a difference between younger and older age-groups in all 4 conditions. Comparing the number of pairs in which a significant difference was shown, the condition with foam rubber, especially with eyes open, tended to highlight age-related changes. In the medial-lateral axis in the eyes open/foam rubber condition, the MF-AUC of the ≥ 75 years group was significantly larger than that of the 65–74 years group, and the MF-AUC of the 65–74 years group was significantly higher than that of the 55–64 years group, although there were no significant differences of MF-AUC among age groups under 54 years. In this condition, although HF-AUC did not change in groups over 35 years old, HF-AUC of each age group over 35 years old was significantly larger than that of the group under 24 years old. This result suggests that, in the medial-lateral axis in the eyes open/foam rubber condition, MF-AUC is specifically affected by age in late-middle-aged (ages 55–64) and older subjects, while HF-AUC is specifically affected by age in early-middle-aged (ages 35–44) subjects.